Guru Sebagai Role Model Pribadi yang Baik dalam Pendidikan dan Pembelajaran di Kelas - Yentidesmyyenti@gmail.com , Desmy; Zurhidayati, Zurhidayati; Satriadi, Inong (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to find out teachers as role models in education and learning in the classroom. This research approach is a qualitative approach with the method used in this article literature study. This research is a type of research that collects data from literature. Primary data was obtained from reading reference books, journals, and websites. Data analysis with the stages of data analysis of the Miles and Huberman model with stages of data reduction, data presentation, and verification or conclusion. The validity test of data in qualitative research includes internal validity, external validity, reliability, and objectivity tests. The findings of this research are that for a teacher to be able to carry out the mandate given to him; he must always get closer to Allah SWT. Being a teacher is a hard job, but in this way the position of a teacher becomes noble. For a teacher to be able to carry out his role well, they must be able to be role models for their students. Teachers must be good individuals who are always the Qur'an and Hadith as a guide in doing and behaving. Some of the behaviors that must be possessed by teachers to become a role for their students include teachers must have strong faith, teachers must have good work quality, and teachers must be useful to others.